2015
DOI: 10.4236/ajps.2015.611181
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Propagation of Grapevine Cultivars with Potential for South of Brazil

Abstract: The micropropation is an important biotechnological tool for obtaining and maintaining mother vine plants with high quality plant health. The objective was to evaluate the establishment and multiplication in vitro and ex vitro acclimatization of grape genotypes with potential for Southern Brazil. Vine nodal segments were cultured in five culture medium formulations without adding growth regulators. It was evaluated the number of leaves and roots, length of roots and shoots, replication rate, relative chlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…9 However, inadequate concentrations of cytokinin can promote the formation of anomalous shoots and multiplication in the form callus, 8 which is undesirable for vegetative propagation protocols, especially the risk of induced somaclonal mutation. Recent study described by Bettoni et al, 3 with Vitis, demonstrate that free salt formulations of growth regulators provided high in vitro multiplication rates and grapevines had root formation in various free culture media growth regulators and or specific phase for rooting. Thus, the aim of this study was to evaluate the establishment and multiplication in vitro in different culture media without adding growth regulators.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…9 However, inadequate concentrations of cytokinin can promote the formation of anomalous shoots and multiplication in the form callus, 8 which is undesirable for vegetative propagation protocols, especially the risk of induced somaclonal mutation. Recent study described by Bettoni et al, 3 with Vitis, demonstrate that free salt formulations of growth regulators provided high in vitro multiplication rates and grapevines had root formation in various free culture media growth regulators and or specific phase for rooting. Thus, the aim of this study was to evaluate the establishment and multiplication in vitro in different culture media without adding growth regulators.…”
Section: Introductionmentioning
confidence: 98%
“…However, the availability of free of pathogens materials is a limiting factor for the sustainability of agricultural production and the permanence in the activity. 3 In this sense, micropropagation techniques are important tools for obtaining and maintaining stock plants of good quality phytosanitary. 4 The process enables the mass multiplication of plants and the formation of free virus matrices; besides preservation materials of interest in an aseptic environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The organogenesis is a biotechnological tool used for obtaining mass production of mother plant with high quality of health (Bettoni et al, 2015). The explants can be grown into whole plant or produce callus.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a favorable commercial scenario, area planted with grapevine and the harvest in the south of Brazil have been declining, it is observed that new vineyards face low productivity and poor quality of grapes due to several complex issues. In relation to plant health, one of the most important obstacles is the infection of vines with viruses, resulting in vine decline and death (BETTONI et al, 2015;GARRIDO et al, 2004).…”
Section: Introductionmentioning
confidence: 99%